Defective lymphocyte caspase-3 expression in type 1 diabetes mellitus - Vendrame, Francesco; Santangelo, Carmela; Misasi, Roberta; Dionisi, Sabrina; Gizzi, Chiara; Realacci, Massimo; Grassetti, Daniele; Di Mario, Umberto; Dotta, Francesco (European journal of endocrinology, 2005)
Objective: Activation-induced cell death (AICD) is a major mechanism in the regulation of peripheral tolerance and its impairment can determine the development of autoimmunity. In the present study, in order to evaluate the role of caspase-3 in type 1 diabetes mellitus (T1DM) AICD, caspase-3 expression was analyzed in peripheral blood lymphocytes from 37 new onset T1DM patients and from 36 normal control subjects (NC) in resting conditions and after anti-Fas-triggered apoptosis. Methods: Caspase-3 expression was determined by semiquantitative RT-PCR and Western blot. Apoptosis was induced in activated lymphocytes by anti-Fas monoclonal antibody and quantified by flow cytometry and morphological analysis. Results: Caspase-3 mRNA expression was reduced in resting lymphocytes in 18/37 T1DM patients and in 1/36 NC (P < 0.01). Patients studied for both Fas-mediated AICD and caspase-3 mRNA expression revealed that a reduced caspase-3 mRNA expression in resting lymphocytes occurred in all patients showing resistance to Fas-mediated apoptosis (T1DM vs NC, P < 0.02) with the exception of 3 patients who exhibited normal caspase-3 expression levels. Caspase-3 protein analysis confirmed mRNA data and showed an impaired expression of caspase-3 active form in T1DM subjects compared with NC. Conclusions: Our data show that defective expression and function of caspase-3 in peripheral lymphocytes of T1DM patients may contribute to the development of AICD resistance in type 1 diabetes.